Improving safety and thermal decomposition performance by the in situ synthesis of core–shell structured ammonium perchlorate/cobalt acetate hydroxide composites. Issue 10 (4th March 2021) - Zhai, Heng; Xu, Pengfei; Li, Yueqi; Ye, Ping; Wang, Ruihao; Guo, Changping; Yang, Guangcheng
Abstract : The AP/Co3 (CH3 COO)5 (OH) composites of the core–shell structure were prepared, the safety and thermal decomposition properties of AP were improved simultaneously, and the possible catalytic mechanism was analyzed. Abstract : At present, the preparation of propellants with high safety and good thermal decomposition performance is still a challenge. An ammonium perchlorate/cobalt acetate hydroxide (AP/Co3 (CH3 COO)5 (OH)) composite was synthesized in situ via liquid deposition. Owing to the barrier effect and heat absorption of cobalt acetate hydroxide, the resulting composite offers reductions in the impact sensitivity and friction sensitivity by 10.2 cm and 96%, respectively. Moreover, with the increase in temperature, cobalt acetate hydroxide coated on the AP surface in situ decomposed into monodisperse CoO nanoparticles around 223 °C, which reduced the high temperature decomposition of ammonium perchlorate from 426.8 °C to 332.8 °C. The real-time FT-IR spectra showed that CoO mainly accelerates the oxidation of ammonia and the conversion of N2 O to NO by promoting electron transfer, thereby catalyzing the thermal decomposition of AP. These confirmed that preparing the AP/Co3 (CH3 COO)5 (OH) composite will lay a foundation for the development of novel high safety performance and high burning rate AP-based solid propellants, showing a broad application prospect.